Management of patients on antithrombotic agents undergoing emergency and elective endoscopy: joint Asian Pacific Association of Gastroenterology (APAGE) and Asian Pacific Society for Digestive Endoscopy (APSDE) practice guidelines - Chan, Francis K.L.; Goh, Khean Lee; Reddy, Nageshwar; Fujimoto, Kazuma; Ho, Khek Yu; Hokimoto, Seiji; Jeong, Young Hoon; Kitazono, Takanari; Lee, Hong Sik; Mahachai, Varocha; Tsoi, Kelvin Kam Fai; Wu, Ming Shiang; et al. (BMJ Publishing Group, 2018)
This Guideline is a joint official statement of the Asian Pacific Association of Gastroenterology (APAGE) and the Asian Pacific Society for Digestive Endoscopy (APSDE). It was developed in response to the increasing use of antithrombotic agents (antiplatelet agents and anticoagulants) in patients undergoing gastrointestinal (GI) endoscopy in Asia. After reviewing current practice guidelines in Europe and the USA, the joint committee identified unmet needs, noticed inconsistencies, raised doubts about certain recommendations and recognised significant discrepancies in clinical practice between different regions. We developed this joint official statement based on a systematic review of the literature, critical appraisal of existing guidelines and expert consensus using a two-stage modified Delphi process. This joint APAGE-APSDE Practice Guideline is intended to be an educational tool that assists clinicians in improving care for patients on antithrombotics who require emergency or elective GI endoscopy in the Asian Pacific region.